Grammatical Category of Version in Georgian and “Conjugation Prefixes” in Sumerian: A Contrastive Analysis - Zurab Baratashvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2018)
In the article semantics, syntactic functions, and morphological marking of the markers of the grammatical category of version in Georgian and of the so-called “conjugation prefixes” in Sumerian are described, analyzed, and contrasted with each other according to different syntactic frameworks. The results are valuable for functional typology.